Pareto improving financial innovation in incomplete markets - Sergio Turner (Brown University, Department of Economics, 2005)
Financial innovation in an existing asset generically supports a Pareto improvement, targeting the income effect. This result, as several on taxation, owes to one unifying notion: that an intervention generically supports Pareto improvements if the implied price adjustment is sufficiently sensitive to the economy's risk aversion. Elul (1995) and Cass and Citanna (1998) introduce financial innovation in a new unwanted asset, targeting the substitution effect. Our result requires an initial position of greater asset completeness, but not the addition of a new asset market. The existence argument relies on recent developments in demand theory with incomplete markets.
Keywords: 330; Finanzinnovation; Unvollkommener Markt; Pareto-Optimum; Wohlfahrtsanalyse; Theorie